Design of a [FeFe] macrocyclic metallotecton for light-driven hydrogen evolution reaction. (24th January 2020) - Rajak, Sanil; Schott, Olivier; Kaur, Prabhjyot; Maris, Thierry; Hanan, Garry S.; Duong, Adam
Abstract: Combining the two most fascinating fields of chemistry in the development of novel metal-organic architectures viz. macrocyclic chemistry and metallotectons, herein, we report the one-pot synthesis of a binuclear Fe(II) macrocyclic metallotecton 2 via coordination-driven assembly in excellent yield and purity. The single crystal structure of 2 indicates two units of cationic iron complex with ligand 1 (6- pyridin-2-yl- [1, 3, 5]-triazine-2, 4-diamine) acting as metallotectons connected to each other by two [μ-PHO3 CH3 ] - bridges forming a [FeFe] macrocycle embedded in two metallotectons. The pyridine and DAT rings of both ligands 1 are nearly coplanar in 2 and each iron(II) has a distorted octahedral geometry. Diaminotriazine groups incorporated in 2 direct multiple hydrogen bonding according to predictable motifs II to produce a final three-dimensional structure. Thermal stability, electronic properties and redox properties of 2 have been studied by thermogravimetric analysis, UV–Vis and cyclic voltammetry respectively. The hydrogen evolution reaction (HER) study of 2 reveals it as an efficient photocatalyst displaying a high turnover number (TON) and turnover frequency (TOF), which is much higher than other Fe based molecular catalysts reported in literature. Also, its photocatalytic activity outperforms the most reported standard reference cobaloxime catalyst (Co III (dmgH)2 (py)Cl). This is by far, the only report showcasing a macrocyclic metallotecton for photocatalytic HER. In addition, complex 2 can be regarded as the next level in supramolecular chemistry as it bridges the gap between macrocycles and metallotectons as well as it can be a future option for our deteriorating environment. Graphical abstract: Image 1 Highlights: Facile one pot synthesis of binuclear [FeFe] macrocyclic metallotecton. Single-crystal structure of the macrocycle displayed fascinating organization. Efficient light-driven hydrogen evolution using a cyclic molecular photocatalyst.